Assessment of external root temperature during root canal irradiation by Nd:YAG and Er:YAG lasers - Barcellos, Daphne Camara [UNESP]; Talge Carvalho, Claudio Antonio [UNESP]; Gomes Torres, Carlos Rocha; Pucci, Cesar Rogerio; Santos Azuma, Claudia Roberta; Pugliesi, Eduardo Nunes (Laser Inst Amer, 2009)
Different types of laser have been widely studied for applicability in the oral health area. In the endodontic area, investigations with some types of laser have been conducted to establish safe parameters for clinical application in root canals. However, it has not been duly explained whether the temperature increase caused by laser irradiation could cause alteration in the temperature on the external surface of the root and, consequently, alterations in the cells of the periodontal ligament, causing resorption and even loss of the dental element. The proposal in this paper was to gauge the external root temperature in the apical and cervical regions of the roots of human teeth during root canal irradiation with Nd:yttrium aluminum garnet (YAG) and Er:YAG lasers using different parameters. The novel approach of this paper is the use of the technique of laser applications along the total length of the root canal with series of repetitive irradiation, however, using time of 1 s of irradiation associated with 1 s off to avoid cumulative thermal effects. Experimental results confirm the accuracy of the parameters and exposure regimen obtained. All the parameters used in this paper are acceptable from a clinical as well as a biological point of view. (C) 2009 Laser Institute of America.
Keywords: Lasers; root canal; surface; temperature